Gender, true crime and the violent subject - Wattis, Louise (Critiquing violent crime in the media, 2021)
The following chapter explores the figure of the serial killer as a spectacular and compelling figure within popular culture. It examines examples from across fact and fiction which have established and perpetuated the serial killer as cultural mainstay, and which evidence our enduring fascination with troubled violent subjects. The discussion also acknowledges variations on this theme, maintaining that while the serial killer almost always retains an element of the spectacular, degrees of attraction, captivation and so forth, do vary in how such figures are constructed and responded to. Moreover, the chapter acknowledges the role of true crime in perpetuating a particular idea of the serial killer, which in turn shapes assumptions that true crime is mainly concerned with macabre murders committed by psychopathic killers and is mainly watched, read and listened to by women. It is argued that not only does this preclude consideration of male audiences of true crime, but it also ignores other types of violent masculine subject. With this in mind, the chapter interrogates the figure of the gangster, often connected to organised crime, who arguably represents a more compelling, attractive and accepted figure within the cultural imaginary, and is further evidence of the ambivalent place of violence and masculinity within popular culture.